High Density Lipoprotein Administration: A New Therapeutic Modality for the Treatment of Cardiovascular Diseases - Sirtori, C. R.; Marchesi, M. (Current Medicinal Chemistry - Immunology, Endocrine & Metabolic Agents, 2005)
Apolipoprotein A-I (apoA-I) is a 243 amino-acid cysteine deficient protein, containing 10 amphipathic domains, that allow its binding to a lipid-rich surface. It is the major protein component of high-density lipoproteins (HDL). Each HDL contains 2 or 3 copies of apoA-I plus various combinations of additional apolipoproteins (e.g. apoE, apoA-IV, apoA-II), lipid transport proteins (e.g. CETP and PLTP), and surface acting enzymes (e.g. paraoxonase, LCAT, PAF). This heterogenous and dynamic class of lipoproteins mainly functions in reverse cholesterol transport, a process resulting in the net removal of excess cholesterol from tissues, to be transported to the liver for excretion. The apolipoprotein AIMilano (A-IMilano) is a rare and naturally occurring variant form of the native apoA-I. The A-IMilano variant was a chance discovery in an individual with very low HDL-cholesterol (7-10 mg/dL) compared to the normal human levels of 40-50 mg/dL. This clinical observation dates back 30 years, and was accompanied by similar findings in two of the proband's children as well as in his father. Surprisingly, these carriers appeared to be remarkably free from any vascular abnormalities. Extensive studies led to the identification of the mutation, a Cysteine for Arginine substitution at position 173, i.e. the first description of a human apolipoprotein mutation associated to altered lipoprotein composition and metabolism. This led to an extensive evaluation of the population of Limone sul Garda for the presence of the mutation and the cardiovascular disease status of the population, confirming the earlier suggestion that this might be a protective variant. In the past 25 years some important additional insights were provided. Particularly, it could be shown that the HDL containing AIMilano is endowed with a remarkably enhanced capacity to remove cholesterol from tissues.
Keywords: recombinant proteins